Analysis of factors influencing the use of digital payments on student purchase levels using Structural Equation Modeling (SEM) - Azahra, Nathania Nabilla; Larasati, Aisyah; Kuswardani, Chintia Dwi Wangsa (Universitas Sultan Ageng Tirtayasa, 2024)
Technological advancements have driven the growth of digital payments, making them increasingly essential in everyday transactions. In Indonesia, Generation Z dominates its usage; however, the system is still evolving and continuously adapting to technological changes and user needs. This study aims to analyze the factors influencing students' interest in adopting digital payment services in Malang City and their impact on purchasing levels. Adapting the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), this research examines Perceived Benefits (PB), Perceived Ease of Use (PEU), Attitude (A), Subjective Norm (SN), and Behavioral Control (BC). Data was collected through a questionnaire distributed to 225 students and analyzed using Structural Equation Modeling (SEM). The results show that Perceived Benefits (PB) and Attitude (A) have a direct influence on students' interest in using digital payments. Additionally, PB and PEU positively and significantly affect Attitude (A). Another key finding reveals that Student Interest has a negative and significant effect on Purchase Level, indicating that students with a high interest in digital payments tend to be more selective in making purchases.